Effects of Nurse Led Group Based Education on Knowledge and Utilization of Antenatal Care Services among Pregnant Women - Noor, Sana; Mukhtar, Madiha; Kaleem, Azeem (Journal of Neonatal Surgery, 2025)
Aims: Aim of the study is to determine the effects of nurse led group based education on knowledge of Antenatal care services among pregnant women. Methods: A quasi-experimental study with a pre-post design was conducted. The study included 58 women aged 20-45, selected through purposive sampling. Data were collected via self-reported questionnaires in Urdu, focusing on demographic information and antenatal care knowledge. Results: The study result showed that majority of participants were aged 25-34 years (62.1%), with a large proportion being housewives (44.8%) and from poor households (56.9%). Knowledge scores significantly improved post-intervention, rising from 8.31±2.76 to 16.40±4.20 (p < 0.001). After the intervention, 58.8% achieved good knowledge compared to 54.2% pre-intervention. Conclusion: The study concluded that nurse led education intervention significantly improve knowledge of pregnant women